Pengaruh Perputaran Piutang,Perputaran Persediaan,Struktur Aktiva,dan Pertumbuhan Penjualan terhadap Profitabilitas Pada Perusahaan Consumer Goods Industry Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2021 - Harangan Sitorus; Nina Purnasari; Ika Wahana Lumban Gaol; Ulfa Nurhayani (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine the effect of Accounts Receivable Turnover, Inventory Turnover, Asset Structure, Sales Growth in consumer goods industry companies listed on the Indonesian Stock Exchange in 2018-2021. Every official data is used from the annual financial reports that come from the IDX. The sampling method uses purposive sampling. There are tests used consisting of classical assumption tests, namely normality tests, multicollinearity, heteroscedasticity, autorelation, panel data regression tests, coefficients (R2), hypotheses (T-test), hypotheses (F-tests). Adjusted R value. square has an influence of 5.6% on Profitability and the remaining 94.4% is influenced by other variables. The results of the research are: (1) receivable turnover, inventory turnover, asset structure variables are not affected by profitability. (2) Sales growth variable has an influence on profitability , (3) Effect of accounts receivable turnover, inventory turnover, asset structure, sales growth simultaneously on profitability. Keywords: Receivable Turnover; Inventory Turnover ; Asset Structure; Sales Network ; Profitability.